The concise new Partridge dictionary of slang and unconventional English (Routledge, 2008)
The Concise New Partridge presents, for the first time, all the slang terms from The New Partridge Dictionary of Slang and Unconventional English in a single volume. With over 60,000 entries from around the English-speaking world, the Concise gives you the language of beats, hipsters, Teddy Boys, mods and rockers, hippies, pimps, druggies, whores, punks, skinheads, ravers, surfers, Valley girls, dudes, pill-popping truck drivers, hackers, rappers and more.